341 LOW INITIATION OF ANTIFRACTURE THERAPY IN BLACK WOMEN. (1st January 2005) - Ryder, K. M.; Shorr, R.; Tylavsky, F.; Bush, A.
Abstract : Background: Health care disparities have been reported in the care of black individuals for numerous medical conditions; however, little is known about black women's receipt of recommended care for low bone mineral density (BMD). Methods: Two-year cohort study of well-functioning community-dwelling older women aged 70-79 residing in Memphis, TN, or Pittsburgh, PA, participating in the Health, Aging, and Body Composition (Health ABC) study between 1997-1999. At the baseline visit a hip DXA scan (Hologic) was performed and an alert letter was sent to participants and their physicians if the DXA revealed osteoporosis. Prescribed and OTC medications were transcribed from drug containers at baseline and annually. The primary end point was use of antiresorptive therapy (ART) or calcium and/or vitamin D (Ca-D). Results: Of 1557 women enrolled in Health ABC, the 371 not using antifracture therapy at baseline with low BMD and/or fracture risk (T-score < -2.0, or a T-score ≤ -1.5 with an additional major risk factor for fracture) constitute the study population. Overall, 29.9% initiated any fracture reducing therapy. Among the 180 white women, 79 (43.9%) initiated any therapy, of which 30 (16.7%) used ART. Of 191 black women, 32 (16.9%) initiated any therapy, and only 17 (8.9%) used ART. In a multivariable model adjusting for factors known to influence use of antifracture therapy, race was one of the strongest predictors (OR 2.61, 1.48-4.61). In an analysis stratified by race, the same factors predicted initiation of therapy in white and black women: receipt of an alert letter documenting low BMD, receipt of a flu shot in the past year, and medication insurance. Conclusion: Too few older women at risk for fracture receive recommended therapy, and the problem is greater among black women. This may be due to lack of guidelines specifically addressing osteoporosis in blacks or patient and physician ignorance of osteoporosis as a health problem in black women. Further research is needed to address this disparity. Acknowledgment: NIA contract numbers N01-AG-6-2101; N01-AG-6-2103; N01-AG-6-2106.